2020
DOI: 10.1111/jch.14098
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in sympathetic nervous system activity and blood pressure in hypertensive patients

Abstract: Increased sympathetic nervous system (SNS) activity leads to increased risk of cardiovascular morbidity and mortality. This study investigated whether there were sex differences in SNS activity among Chinese patients with hypertension. Ethnic Chinese non‐diabetic hypertensive patients aged 20–50 years were enrolled in Taiwan. A total of 970 hypertensive patients (41.0 ± 7.2 years) completed the study, 664 men and 306 women. They received comprehensive evaluations including office blood pressure (BP) measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The APOE rs7412T/T genotype was found to be a risk factor for hypertension in this study. It has been reported that hypertensive patients have higher catecholamine levels [ 52 , 53 ]. The results of this study showed that APOE rs7412T/T subjects had higher catecholamine levels than C/C subjects, but there was no statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The APOE rs7412T/T genotype was found to be a risk factor for hypertension in this study. It has been reported that hypertensive patients have higher catecholamine levels [ 52 , 53 ]. The results of this study showed that APOE rs7412T/T subjects had higher catecholamine levels than C/C subjects, but there was no statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…e APOE rs7412T/T genotype was found to be a risk factor for hypertension in this study. It has been reported that hypertensive patients have higher catecholamine levels [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Second, IR stimulates pro-opiomelanocortin (POMC)-releasing neurons in the arcuate nucleus of the hypothalamus, and activates glutamatergic neurons and neurons that express melanocortin 4 receptor (MC4R) in the paraventricular nucleus; thus enhancing the overall activity of the sympathetic nervous system [ 42 , 43 ]. The vasodilatory effect observed in hypertensive patients is thus impaired, with sympathetic nerve activation three times that in normal, unaffected individuals [ 44 ]. Lin et al uncovered IR as an alarming cause of impaired glucose metabolism and dyslipidemia in the body [ 45 ], and Feng indicated that IR was directly correlated with triglycerides and total cholesterol in Chinese patients [ 46 ].…”
Section: Discussionmentioning
confidence: 99%